Isoeritrólise neonatal eqüina - Rossi, Larissa Sartori [UNESP] (2009)
Equine neonatal isoerythrolysis is a neonatal foals’ illness. Results from the incompatibility of blood type between the foal and the mare and mediated by maternal antibody absorbed by the colostrum against foal’s red blood cells. Characterized by a type ll hypersensitivity reaction, where the exhibition of the organism to a strange antigen, that it takes the sensitization of the lymphocytes B that after the removal of the antigens by the reticule-endothelial system the production of immunoglobulin is decreased, with the formation of cellular immunological will cause the occurrence of the illness in foal of sensitized mares. The most important clinical signs are severe anemia and jaundice, and this illness should be differentiated of other as: hemolysis induced by bacterial toxins, diseases of the hepatobiliary system, disseminated intravascular coagulation and incompatibility in blood transfusions. Like the sensitization happens during the previous incompatible foal’s birth, most cases occur in foals of multiparous mares. However during the first pregnancy the mare can generate a foal with neonatal 7 isoerythrolysis if she have developed placental anomaly in the beginning of the pregnancy which blood cells in her circulation